2012
DOI: 10.1002/clen.201100635
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrogen Oxides, Black Carbon, and Meteorological Parameters on the Variation of Surface Ozone Levels at a Tropical Urban Site – Hyderabad, India

Abstract: In this study, temporal variations of surface ozone (O3) were investigated at tropical urban site of Hyderabad during the year 2009. O3, oxides of nitrogen (NOx = NO + NO2), black carbon (BC), and meteorological parameters were continuously monitored at the established air monitoring station. Results revealed the production of surface O3 from NO2 through photochemical oxidation. Averaged datasets illustrated the variations in ground‐level concentrations of these air pollutants along different time scales. Maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Control day data is an average of 3 days before and after lightning day. The diurnal mean data of monthly mean showed a typical variation in NO x with morning and evening peak concentrations attributing to traffic emissions (Swamy et al 2012;Yerramsetti et al 2013b). Besides this, low wind speed and high relative humidity had contributed to localization of trace gases, resulting in higher concentration at peak hours.…”
Section: Variations In Surface O 3 and No X During Thunderstorms In Tmentioning
confidence: 97%
See 1 more Smart Citation
“…Control day data is an average of 3 days before and after lightning day. The diurnal mean data of monthly mean showed a typical variation in NO x with morning and evening peak concentrations attributing to traffic emissions (Swamy et al 2012;Yerramsetti et al 2013b). Besides this, low wind speed and high relative humidity had contributed to localization of trace gases, resulting in higher concentration at peak hours.…”
Section: Variations In Surface O 3 and No X During Thunderstorms In Tmentioning
confidence: 97%
“…In most of the events, the lightning intensity was high during post-noon to evening hours (14:00 to 20:00 h Indian Standard Time, IST), which might be due to surface heating by local convection (Sen Roy and Balling 2013). Although anthropogenic emissions are major sources of NO x at the monitoring site (Yerramsetti et al 2013b), significant variations in the concentrations of NO x and O 3 were observed during lightning events.…”
Section: Electric Field Measurementsmentioning
confidence: 98%
“…However, the destruction of O 3 has been observed with increasing NO x concentration, particularly in the urban lower tropospheric region (Yerramsetti et al 2013a). Relationship between NO x and VOCs on the formation of O 3 revealed that reduced VOCs/NO x ratios can enhance titration reaction of O 3 (Swamy et al 2012).…”
Section: Ozone Formation Potential Of Vocsmentioning
confidence: 98%
“…On the other hand, rainfall scavenging during monsoon often lowers the overall aerosol loading of the atmosphere [23]. Anthropogenic industrial and automotive sources have a large impact on aerosol loading over the urban, densely industrialized sites such as Hyderabad or Bangalore [24,25]. Increased biomass burning during the cooler winter months leads to an increase in aerosol loading over several urban sites, such as Kolkata [26].…”
Section: In Situ Ssr Measurementsmentioning
confidence: 99%